Biodegradasi Substrat Gergajian Kayu Sengon oleh Jamur Kelompok Pleurotus Asal Bogor Biodegradation of Sengon-wood Sawdust Substrate by Pleurotus Group Fungi from Bogor - Elis Nina Herliyana; Dodi Nandika; Achmad Lisdar; I. Sudirman; Arief B. Witarto (Masyarakat Peneliti Kayu Indonesia, 2008)
White-rot fungi has been started to be developed for enhancing the mushroom based industry in many countries including in environmentally sound of bio-bleaching and bio-pulping technological process. Six isolates of wild Pleurotus group were isolated from various location in Bogor, namely Pleurotus EAB7, EB24, EB14-2, EB6, EA4 and EB9 of which were studied of their ligninolytic character. P. ostreatus HO was used as standard comparison.The ligninolytic character of these six fungi isolates was measured after inoculation into Sengon (Paraserianthes falcataria) wood sawdust substrate inside plastic bag with substrate weight of about 400 gram; other additional substances were paddy scalp, gypsum, calcium and water. Observation was done on Sengon wood sawdust substrate since vegetative phase until reproductive phase. Samples were opened, destructed with Hammer Mill, and then dried with oven on temperature of 40oC in 4 6 days until water content reach 15%, and weigh about 30 gram for analyses. Analyses were done by measuring water soluble extractive substance (TAPPI T 207 om-88 Standard), NaOH (sodium hydroxide) 1% soluble extractive substance (TAPPI T 212 om-88 Standard), alkohol-benzena soluble extractive substance (TAPPI T 204 om-88 Standard), lignin content (TAPPI T 13 os-54 Standard), holocellulose content with method browning (TAPPI T 211 m Standard), and cellulose content with method Cross and Bevan (Meulenhoff et al. 1977; TAPPI 1996).Having applied of each wild Pleurotus group isolates resulted in increasing of extractives total compounds both in vegetative and reproductive phases. Each wild Pleurotus group isolates shows variation in decreasing average of lignin content (10.7 89.7%) and cellulose (18.9 87.4%). Pleurotus EB9 are able to decrease the highest lignin (89.7%) and cellulose (87.4%) content of substrate. Classification based on ligninolytic character is different with classification based on morphological and physiological characters. Pleurotus EB9 seems to be separated from other isolates. This shows that there was different ligninolytic character among the isolates. The best isolate for bio-pulping and bio-bleaching agent is Pleurotus EB9 on vegetative phase.